A 3-D nanoribbon-like Pt-free oxygen reduction reaction electrocatalyst derived from waste leather for anion exchange membrane fuel cells and zinc-air batteries. Issue 16 (9th April 2019) - Soni, Roby; Bhange, Siddheshwar N.; Kurungot, Sreekumar
Abstract : In this work, leather is used as a single source of carbon and heteroatoms to derive a 3-D nanoribbon-like ORR electrocatalyst for AEMFC and zinc–air battery. Abstract : Fe–N x and Fe–S-based ORR electrocatalysts have emerged as rightful candidates to replace Pt in fuel cells to make the technology cheap and sustainable. Fe–N–C catalysts are generally prepared by the pyrolysis of conducting polymers, metal–organic frameworks, aerogels, etc ., and the combination of multiple heteroatoms and metal precursors. These precursors are mostly expensive and their synthesis involves multiple steps. In this report, we have demonstrated the synthesis of a Fe–N–C catalyst from the waste leather obtained from the footwear and other leather-consuming industries. The pyrolysis of leather with FeCl3 (metal source) results in the formation of a highly thin and porous nano-ribbon like morphology. Waste leather acts as a cost-free single source of heteroatoms like N, S and carbon. The catalyst synthesized at a temperature of 900 °C shows an overpotential of 40 mV and better durability compared to the commercial Pt/C catalyst. The catalyst is demonstrated as the cathode for alkaline exchange membrane fuel cell (AEMFC) and zinc–air battery (ZAB) applications. In the AEMFC, a power density of 50 mW cm −2 and an OCV of 0.92 V are obtained whereas, in the ZAB, it exhibited a power density of 174 mW cm −2 compared to 160 mW cm −2 of the system based on the Pt/C catalyst.